Identyfikacja potencjalnych źródeł efektów synergicznych w zarządzaniu procesami fuzji i przejęć - Staniszewski, Andrzej (The identification of potential sources of effects synergism in management the processes of fusion and take over, 2005)
The enterprise in present article was introduced the test of identification of potential sources effects the synergism in functional areas the management. These areas were distinguished, which should be object of buyer's interests in aim of establish of common points reference joining firms as well as real qualification of sources and value co-operate. Such approach guarantees the adequate pricing of transaction how it permits to estimate also or the connection of firms will bring in range the provide of advantage tire utilization of common economic potential, deepening key competences and building strong competitive position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 450-457